Association Between Socioeconomic and Demographic Characteristics and Non-fatal Alcohol-Related Injury in Maringá, Brazil - El-Gabri, Deena; Toomey, Nicole; Gil, Nelly Moraes; de Oliveira, Aline Chotte; Calvo, Paulo Rafael Sanches; Tchuisseu, Yolande Pokam; Williams, Sarah; Andrade, Luciano; Vissoci, Joao Ricardo Nickenig; Staton, Catherine (Frontiers in Public Health, 2020)
Background: Previous research has corroborated a high burden of alcohol-related injury in Brazil and the presence of socioeconomic disparities among the injured. Yet individual-level data is scarce. To fill this gap, we examined the association between demographic and socioeconomic characteristics with non-fatal alcohol-related injury in Maringá, Brazil. Methods: We used household survey data collected during a 2015 cross-sectional study. We conducted univariate and multivariate analysis to evaluate associations of demographic (age, gender, race) and socioeconomic characteristics (employment, education, income) with non-fatal alcohol-related injury. Results: Of the 995 participants who reported injuries, 62 (6.26%) were alcohol-related. Fifty-three (85%) of alcohol-related injuries were reported by males. Multivariate analysis indicated being male (OR= 5.98 95% CI = 3.02, 13.28), 15-29 years of age (OR= 3.62 95% CI = 1.72, 7.71), and identifying as Black (OR= 2.38 95% CI = 1.09, 4.95) were all significantly associated with increased likelihood of reporting an alcohol-related injury whereas unemployment was significantly associated with decreased likelihood of reporting an alcohol-related injury (OR= 0.41 95% CI = 0.18, 0.88). Conclusion: Our findings suggest that in Maringa, being male, between the ages of 15 and 29, employed, or identify as Black were associated with higher risk for non-fatal alcohol-related injury. Individual level data, such as ours, should be considered in combination with area-level and country-level data when developing evidence-based public-health policies.